2003
DOI: 10.1016/s0035-9203(03)80007-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the determinants of tuberculosis control in resource-poor countries: insights from a qualitative study in The Gambia

Abstract: Despite the availability of effective treatment, tuberculosis (TB) remains a major cause of death from an infectious disease in the world, particularly in resource-poor countries. Among the chief reasons for this are deficiencies in case tracing and in adherence to treatment. In order to investigate the contribution of non-biological factors to these deficiencies, we carried out a qualitative study in The Gambia, West Africa, from October 2000 to March 2001. The methods used were focus group discussions, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 15 publications
3
42
2
Order By: Relevance
“…Therefore, it is essential to include HIV infection as a risk factor when trying to identify the role of other factors on the risk of developing TB. 14 We observed a consistent effect of former experience of TB within the household, and this effect increased with the number of persons who had TB in the past. Furthermore, there was some evidence that this effect was higher when the former TB case was in close family link with the index TB case, as compared with unrelated household members.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, it is essential to include HIV infection as a risk factor when trying to identify the role of other factors on the risk of developing TB. 14 We observed a consistent effect of former experience of TB within the household, and this effect increased with the number of persons who had TB in the past. Furthermore, there was some evidence that this effect was higher when the former TB case was in close family link with the index TB case, as compared with unrelated household members.…”
Section: Discussionsupporting
confidence: 60%
“…8 There are considerable sex differences with regard to stigma and its social consequences, which may result in differential healthseeking behaviour and access to care between males and females. 9,10 However, the consistent effect of male gender observed, both with household and community controls and throughout the sites, suggests that selective under-diagnosis relating to gender is unlikely. Of note, a genome-wide linkage study searching for regions of the human genome containing TB susceptibility genes suggested a linkage between regions of the chromosome X and TB, with a lod score of 1.77, which could contribute to the excess of TB in males in many populations.…”
Section: Discussionmentioning
confidence: 89%
“…This proved especially difficult for patients with severe symptoms [2225]. One study noted that access to health care facilities was better in urban areas than rural areas [26], and both patients [27,28] and providers [29] noted that adherence was compromised if the distance from patients' homes to the nearest clinic was too great. If patients' homes were close to a clinic, however, the patients could attend regularly [30].…”
Section: Resultsmentioning
confidence: 99%